2015
DOI: 10.1186/s40064-015-1423-7
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation of TRIM9 as a marker for detection of circulating tumor DNA in breast cancer patients

Abstract: The aim of the present study was to investigate the promoter methylation status of TRIM9 in breast cancer and to determine the presence of TRIM9-methylated circulating tumor DNA (ctDNA) in plasma. Bisulfite sequencing with a next generation sequencer showed TRIM9 promoter methylation in 92 % (11/12) of breast cancer cell lines (BCCs) and 68 % (13/19) of breast tumor tissues but not in any normal breast tissues (0/19). Methylation ratio of TRIM9 was significantly lower in basal type (9 %, n = 23) than luminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Strategies used in DNA methylation analysis can be classified into two groups: site-specific and genome-wide methylation detections. Currently, detection of site-specific methylations of DNA has been conduced more often [14] , [153] , [154] , [155] . Many methods originally used for site-specific detection of genomic DNA methylations are suitable for site-specific detection of ctDNA methylations as well.…”
Section: Methods For Detecting Ctdnasmentioning
confidence: 99%
“…Strategies used in DNA methylation analysis can be classified into two groups: site-specific and genome-wide methylation detections. Currently, detection of site-specific methylations of DNA has been conduced more often [14] , [153] , [154] , [155] . Many methods originally used for site-specific detection of genomic DNA methylations are suitable for site-specific detection of ctDNA methylations as well.…”
Section: Methods For Detecting Ctdnasmentioning
confidence: 99%
“…Recently, an analysis of the number of driver and passenger mutations in cancers revealed a generally greater number of aberrations in DNA methylation compared to the number of somatic mutations (several hundreds to 1,000 vs. up to 80, respectively, per tumor) . Furthermore, reports have indicated that DNA methylation patterns are effective tumor markers , and DNA methylation‐based biomarkers might facilitate the detection of cancer at very early stages of tumorigenesis . In fact, our data suggested that DNA methylation was strongly associated with tumorigenesis in hiPSC‐NS/PCs, even those that had been passaged relatively few times (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Methylation profiling of cfDNA has been investigated in cancer diagnostics and assessment of therapeutic outcomes [18][19][20][21][22][23][24]. Guo et al have shown that identifying methylation patterns from cfDNA can be used to map tissue-of-origin in lung and colorectal cancer patients [25].…”
Section: Discussionmentioning
confidence: 99%